2013
DOI: 10.1177/1077801213498216
|View full text |Cite
|
Sign up to set email alerts
|

College Men’s and Women’s Respective Perceptions of Risk to Perpetrate or Experience Sexual Assault

Abstract: The present study examines alcohol use, expectancies (i.e., beliefs about the outcomes of alcohol consumption), and college men’s (n = 127) and women’s (n = 191) respective perceptions of risk to perpetrate/experience sexual violence. Interactions between alcohol consumption and expectancies were examined. Alcohol expectancies regarding assertiveness increased women’s perceived risk for sexual intercourse via alcohol/drugs. Among women reporting high alcohol use, global expectancies were positively associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 73 publications
0
17
1
1
Order By: Relevance
“…Results were consistent with previous research suggesting that women with sexual assault histories drink more than women without a history of sexual assault (Grayson & Nolen-Hoeksema, 2005; Kilpatrick et al, 2000; Gidycz et al, 2007). Surprisingly, these results are not consistent with previous findings that the more women drink, the higher they estimate their sexual assault risk (McCauley & Calhoun, 2008; Gidycz et al, 2007; Untied et al, 2013). It is further surprising that drinking to cope and typical weekly drinking were not associated with when to leave a hypothetical sexual assault scenario for the full sample.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Results were consistent with previous research suggesting that women with sexual assault histories drink more than women without a history of sexual assault (Grayson & Nolen-Hoeksema, 2005; Kilpatrick et al, 2000; Gidycz et al, 2007). Surprisingly, these results are not consistent with previous findings that the more women drink, the higher they estimate their sexual assault risk (McCauley & Calhoun, 2008; Gidycz et al, 2007; Untied et al, 2013). It is further surprising that drinking to cope and typical weekly drinking were not associated with when to leave a hypothetical sexual assault scenario for the full sample.…”
Section: Discussioncontrasting
confidence: 99%
“…It is not clear whether increased risk for ASA in problem drinkers is related to risk perception. Women who report heavy drinking perceive themselves to be at higher risk of future ASA than nondrinkers (McCauley & Calhoun, 2008; Gidycz, et al, 2007; Untied et al, 2013). However, acute alcohol intoxication can dampen discomfort related to cues of sexual assault risk (Davis et al, 2009).…”
Section: Maladaptive Coping Strategiesmentioning
confidence: 99%
“…Furthermore, women’s engagement in sexual activity might help explain pathways between perceived future control and perceived future likelihood of assault recurrence, wherein women’s perceived control over future similar victimization experiences might lead them to engage in sexual activity, thereby increasing their perception of future risk. Women who report current alcohol usage and prior experiences of sexual victimization also perceive that they are more vulnerable to assault recurrence (Untied, Orchowski, & Lazar, 2013). Thus, the moderating effect of these variables merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses indicated that higher weekly alcohol use increased women's perceived risk to experience sexual intercourse as a result of a man's authority or administration of alcohol, i.e. women who were heavy drinkers perceived themselves at higher risk for sexual victimization than nondrinkers (40). On the contrary, in younger and less experienced people (students) in general, problematic use of alcohol is associated with novelty and popularity seeking (41) and hence with more risky behaviors.…”
Section: Resultsmentioning
confidence: 99%